2021
DOI: 10.3892/mco.2021.2270
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of preoperative red cell distribution width on the survival of patients who have undergone surgery for non‑small cell lung cancer

Abstract: Red cell distribution width (RDW) is a prognostic factor for various malignancies, including colorectal, breast and lung cancer. The effect of preoperative RDW on the prognosis of patients who have undergone surgery for non-small cell lung cancer (NSCLC) was investigated in the present study. This retrospective, single-institution study included consecutive patients who had undergone complete NSCLC resection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, Liu et al conducted a study with 750 stage I–III patients (stage I: n = 352, stage II: n = 134, stage III: n = 264) to explore the prognostic value of RDW, with more than half of the cases being AD (401/750) [ 34 ]. Matsui et al also performed a study with 338 stage I–III patients (stage I: n = 289, stage II: n = 44, stage III: n = 5), and up to 70.38% of the cases were AD (259/338) [ 35 ]. To date, only two studies have reported the prognostic value of RDW (226 AD, 47 others [ 14 ]; 166 AD [ 15 ]) in stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al conducted a study with 750 stage I–III patients (stage I: n = 352, stage II: n = 134, stage III: n = 264) to explore the prognostic value of RDW, with more than half of the cases being AD (401/750) [ 34 ]. Matsui et al also performed a study with 338 stage I–III patients (stage I: n = 289, stage II: n = 44, stage III: n = 5), and up to 70.38% of the cases were AD (259/338) [ 35 ]. To date, only two studies have reported the prognostic value of RDW (226 AD, 47 others [ 14 ]; 166 AD [ 15 ]) in stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Among many examinations, including physical examination and imaging examination, the value of routine laboratory parameters (such as RDW) is often underestimated. There has been an increase in the use of simple and inexpensive RDW tests in whole blood over the past few years to help predict many disease (25)(26)(27). As we all know, there are still a small portion of patients with cerebral infarction who suffer from serious conditions such as post-thrombotic hemorrhage after receiving thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%